[Translated article] Rivaroxaban versus enoxaparin for thromboprophylaxis in orthopedic surgery: A meta-analysis - O. Abad Vélaz; I. Carbonel Bueno (Revista Española de Cirugía Ortopédica y Traumatología, 2025)
Introduction: Venous thromboembolism is highly associated with orthopedic surgery, so thromboprophylaxis is an important consideration for orthopedic surgeons. The new oral anticoagulants have clear advantages for clinical practice. Objectives: To analyze the efficacy and safety of rivaroxaban versus enoxaparin for thromboprophylaxis in different orthopedic surgeries. Material and methods: Systematic electronic search of clinical trials was carried out. Data extraction of efficacy outcomes (deep venous thrombosis, pulmonary embolism and death) and safety outcomes (major bleeding and clinically relevant bleeding) was realized. Results: Six randomized and controlled clinical trials were included in this meta-analysis. Compared with enoxaparin the risk of venous thromboembolism was lower with rivaroxaban both in different orthopedic surgeries (RR: 0.51; 95% CI: 0.36–0.73; p = .0002). This result was even better and more homogeneous in the analysis of symptomatic deep venous thrombosis outcome (RR: 0.43; 95% CI: 0.28–0.65; p < .0001; I2 = 0%; p = .49). The risk of bleeding was not significantly higher with rivaroxaban (RR: 1.20; 95% CI: 0.97–1.49; p = .09). Conclusions: Rivaroxaban should be considerate such as a more effective alternative for thromboprophylaxis in orthopedic surgery. Resumen: Introducción: La enfermedad tromboembólica venosa está altamente asociada a las intervenciones ortopédicas, siendo la tromboprofilaxis una prioridad para el cirujano ortopédico. Los nuevos anticoagulantes orales presentan ventajas claras para la práctica clínica diaria. Objetivos: Analizar la eficacia y la seguridad del rivaroxabán frente a la enoxaparina como tromboprofilaxis tras distintas intervenciones ortopédicas. Material y métodos: Se realizó una búsqueda bibliográfica sistematizada de ensayos clínicos. Se recogieron los datos de variables de eficacia clínica (trombosis venosa profunda asintomática o sintomática, embolia pulmonar, muerte) y seguridad clínica (hemorragia mayor, hemorragia clínicamente relevante). Resultados: Seis ensayos clínicos aleatorizados fueron seleccionados para el metaanálisis. El rivaroxabán mostró una mejor eficacia clínica tras distintas intervenciones ortopédicas (RR: 0,51; IC 95%: 0,36-0,73; p = 0,0002). Se observó mayor beneficio y homogeneidad en los resultados al analizar únicamente la trombosis venos profunda sintomática (RR: 0,43; IC 95%: 0,28-0,65; p < 0,0001; I2 = 0%; p = 0,49). Además, no se apreció mayor riesgo hemorrágico estadísticamente significativo con el rivaroxaban (RR: 1,20; IC 95%: 0,97-1,49; p = 0,09). Conclusiones: El rivaroxabán debería ser considerado como una alternativa terapéutica más eficaz respecto a la enoxaparina empleada de manera rutinaria en nuestro entorno.